Detection of multiple drug-resistant Trypanosoma congolense populations in village cattle of south-east Mali - Mungube, E.O.; Vitouley, H.S.; Cudjoe, E.A.; Diall, O.; Boucoum, Z.; Diarra, B.; Sanogo, Y.; Randolph, Thomas F.; Bauer, B.; Zessin, K.H.; Clausen, Peter-Henning (Springer, 2012)
Background Tsetse fly-transmitted African animal trypanosomosis causes annual losses that run into billions of dollars. The disease is assumed to cause hunger and poverty in most sub-Saharan countries since it represents a serious impediment to sustainable livestock production. Both a cross-sectional and a longitudinal study were carried out from November to December 2007 to evaluate trypanosomosis risk and susceptibility of trypanosomes to trypanocidal drug treatment in village cattle populations in south-east Mali. Methods Eight purposively selected villages participated in the study. In each village, eight traps deployed along drainage lines over 24-hour duration were used to trap tsetse. One hundred systematically selected cattle in the study villages were examined for trypanosomes. All trypanosome-positive cattle were randomly allocated into two treatment groups: a group treated with 0.5 mg/kg bw. isometamidium chloride (ISMM) and a group treated with 3.5 mg/kg bw. diminazene aceturate (DIM). The cattle were monitored for trypanosomes at day 14 and 28 post-treatment. Results Of the 796 cattle examined, 125 (15.7%) were trypanosome-positive. Village trypanosome prvalences ranged between 11% and 19%. There were no significant (p>0.05) differences in the village trypanosome prevalences. Trypanosoma congolense was the dominant trypanosome species accounting for 73% (91/125) of the infections and T. viax the remainder. Twenty (31.7%) of the 63 cattle on 0.5 mg/kg bw. ISMM treatment still had trypanosomes 14 days post-treatment. Of the 43 aparasitaemic cattle monitored to day 28, 25.6% (11) became parasitaemic resulting in a cumulative failure rate of 49.2% (31/63). Trypanosoma congolense accounted for 77.4% (24/31) of failed ISMM treatments. The 62 cattle treated with 3.5 mg/kg bw. DIM resulted in 30.6% (19/62) failed treatments. Although 42.2% (19/45) of T. congolense positive cattle had failed DIM treatment, all T. vivax positive cattle responded positively to DIM treatment. Conclusion Despite the overreliance on trypanocides in the control of trypanosomosis, multiple drug-resistant Trypanosoma congolense populations detected in villages in south-east Mali makes the use of drugs doubtful. Effective alternative methods for trypanosomosis control ought to substitute chemotherapy to ensure sustainable cattle production in these villages. Since there is no single strategy for containing trypanocidal drug resistance, promotion of an integrated approach combining proven trypanosomosis control approaches in high trypanosomosis risk areas is most desirous. The best-bet strategy this study recommended for areas with multiple drug resistance included area-wide community tsetse control, control of co-infections to exploit self-cure against resistant trypanosome populations and the rational use of trypanocidal drugs which should be urgently promoted at all levels as a way of containing or reversing resistance.